Dampak Penginjilan Terhadap Pertobatan Mahasiswa di Lembaga Pelayanan Pemimpin Indonesia - Tonni Hutasoit; Djone Georges Nicolas; Linda Susanthi; Jona Bungaran Sinaga; Ramses Manurung (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study is to examine how the impact of evangelism on student conversions at the Indonesian Leaders Service Institute. In conducting this research, the author uses qualitative and quantitative methods by collecting data through direct questions with students who are members of the Indonesian Leadership Service Institute as well as through the Bible and various books and journals. At first before these students joined the Indonesian Leadership Service Institute 99% of them had not experienced conversion, due to several factors as follows: They did not know the importance of being born again and felt they had become Christians because they were born into a Christian family, besides that they think that if they are baptized, they will definitely go to heaven, and their activeness in worship and being actively involved in church services is enough to represent their faith in God. However, after the students were evangelized at the Indonesian Leaders Service Institute (LPPI). So the result is, that the number of students who want to repent and accept Jesus in their hearts personally through services since 2000-2020 has accumulated 20,000 people